2001
DOI: 10.1128/mcb.21.9.3083-3095.2001
|View full text |Cite
|
Sign up to set email alerts
|

Role of NF-Y in In Vivo Regulation of the γ-Globin Gene

Abstract: The duplicated CCAAT box is required for ␥ gene expression. We report here that the transcriptional factor NF-Y is recruited to the duplicated CCAAT box in vivo. A mutation of the duplicated CCAAT box that severely disrupts the NF-Y binding also reduces the accessibility level of the ␥ gene promoter, affects the assembly of basal transcriptional machinery, and increases the recruitment of GATA-1 to the locus control region (LCR) and the proximal promoter and the recruitment of transcription cofactor CBP/p300 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 38 publications
5
43
0
Order By: Relevance
“…We recently found that NF-Y bound at the CCAAT motifs in the ␤-globin ERV-9 LTR enhancer could recruit other transcription factors including GATA-2 to the LTR enhancer (X.Y., unpublished results). NF-Y bound at the CCAAT motif has been reported to preset and remodel chromatin structure of the promoter in oocytes (37) and erythroid progenitor cells (38). It is thus possible that the ERV-9 LTRs in the human genome recruit NF-Y in the assembly of transcription complexes, which could initiate transcription of LTR RNAs into the downstream genomic DNAs to preset chromatin structure of the cis-linked gene loci in oocytes and adult stem͞progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that NF-Y bound at the CCAAT motifs in the ␤-globin ERV-9 LTR enhancer could recruit other transcription factors including GATA-2 to the LTR enhancer (X.Y., unpublished results). NF-Y bound at the CCAAT motif has been reported to preset and remodel chromatin structure of the promoter in oocytes (37) and erythroid progenitor cells (38). It is thus possible that the ERV-9 LTRs in the human genome recruit NF-Y in the assembly of transcription complexes, which could initiate transcription of LTR RNAs into the downstream genomic DNAs to preset chromatin structure of the cis-linked gene loci in oocytes and adult stem͞progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…To examine whether the V205M mutation reduces GATA-1 access to sites other than the ␤-major promoter, we examined HS2 and HS4 of the LCR, which, like HS3, are bound by GATA-1 in vivo (33)(34)(35). We found that although FOG-1 binding appears to be dispensable for GATA-1 access to HS4 (Fig.…”
Section: Fog-1 Requirement For Gata-1-er Occupancy At Erythroid Regulmentioning
confidence: 99%
“…ChIPs were performed as described (24,25) with minor modifications. One spleen, or brain, or six yolk sacs were used per condition.…”
Section: Methodsmentioning
confidence: 99%